PLANTING MEDIUM VARIATION IN AQUAPONIC SYSTEM OWN GROWTH AND YIELD OF RED CHILI (Capsicum annum L.) - Maimunah Siregar; Bambang Surya Adji Syahputra (Agric, 2022)
Red chili (Capsicum annum L) is a kind of horticulture that has been high economic and nutrient value, so it’s impotent to increase the yield. With the modern technology in agriculture, many farmers have been planting without using soil such as aquaponics, especially for vegetables. This study aims to determine the most suitable planting media for the growth and yield of 3 red chili varieties. This research was used a factorial Randomized Complete Block Design (RCBD) with 3 replicates, which first factor was used 4 growing media (Cocopeat, husk charcoal, tankos and a combination of all) and the second factor was used 3 varieties of red chili (Kirana, pasemah and terano). Parameters measured; plant height, number of leaves, number of branches, number of fruits and weight of fruits. Tankos media and terano variety have a significant effect on plant height and leaf number, during the 4 weeks of observation. The number of branches and number of fruit, for both the treatments of the planting media and the varieties, were not significantly different, but the yield was significantly different as compared among them with terano was the better. It is clearly that, for high yield is terano variety, while the good medium is tankos. Of all the parameters observed, there was no interaction between media with varieties. Key words : Aquaponic, planting media, varieties, red chili